2004
DOI: 10.1097/01.prs.0000131877.52740.0e
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Breast Reconstruction in Women with Bilateral Prophylactic Mastectomy: A Descriptive Study

Abstract: Prophylactic bilateral mastectomy is an option for women who are at an increased risk of developing breast cancer. Prophylactic mastectomy is often performed with immediate reconstruction (i.e., at the same time and under the same anesthetic as the mastectomy). Satisfaction with reconstruction has been described previously for women with mastectomy for breast cancer. However, the authors know of no previous research that has reported on satisfaction with reconstruction in patients who have electively sought ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 26 publications
2
19
0
3
Order By: Relevance
“…1 In particular, poor cosmetic results or complications have correlated with patient dissatisfaction. 2,3 Prior studies of breast reconstruction methods have produced somewhat conflicting results in terms of outcomes. Some studies have shown higher satisfaction rates for autologous tissue reconstruction compared with implant reconstruction.…”
mentioning
confidence: 98%
“…1 In particular, poor cosmetic results or complications have correlated with patient dissatisfaction. 2,3 Prior studies of breast reconstruction methods have produced somewhat conflicting results in terms of outcomes. Some studies have shown higher satisfaction rates for autologous tissue reconstruction compared with implant reconstruction.…”
mentioning
confidence: 98%
“…3,6 Despite the well-known finding of increased complications and the potential for decreased aesthetic outcomes in patients receiving postmastectomy radiation therapy after both implant and autologous reconstruction, the authors report similar general and aesthetic patient satisfaction between the unilateral and bilateral reconstruction groups. 7-10 Regardless of the increased complications seen in irradiated patients undergoing breast reconstruction, patient satisfaction scores have been reported by this group and others to be equivalent to those of nonradiated patients.…”
mentioning
confidence: 43%
“…Preoperative psychosocial functioning, body image, and physical activity levels have been shown to influence patient satisfaction with breast reconstruction. [3][4][5] Patients who are relatively satisfied preoperatively generally are pleased postoperatively, regardless of whether or not a reconstruction is performed. Prospective satisfaction assessments and evaluation of satisfaction over time are imperative to support the authors' conclusions.…”
mentioning
confidence: 98%
“…They concluded that radiotherapy was beneficial for patients with a T1N1 tumour and a lymphnode ratio of >0.08, and patients with a T2N1 tumour and a lymphnode ratio of >0. 25.…”
Section: Indications For Postmastectomy Radiotherapymentioning
confidence: 95%
“…Studies have shown that reconstruction post-mastectomy can improve the psychosocial outcomes of these patients. 3,24,25 A randomized controlled trial conducted in 1983 showed that psychological morbidity is reduced by immediate reconstruction in patients undergoing mastectomy for breast carcinoma. 3 It is important to note that this study was methodologically flawed, and the lack of patient control over timing and method of reconstruction is "concerning", as alluded to in a Cochrane review 26 in which this study is included.…”
Section: Breast Reconstruction and Radiotherapymentioning
confidence: 99%